Linguocultural studies as intercultural communication factor - Moiseeva, S. A.; Оgneva, H. A. (Cognition, Communication, Discourse, 2018)
In the article the influence of translation of belles-lettres fiction on the process of intercultural communication is considered. The role of the language personality of the translator in the process of overcoding the work of literature is determined. The reasons of partial adaptation of culturally marked text units to the perception of a foreign culture reader are defined.